2018
DOI: 10.1002/ejlt.201800221
|View full text |Cite
|
Sign up to set email alerts
|

Phenolics, Tocopherols, and Volatiles Changes During Virgin Pistachio Oil Processing Under Different Technological Conditions

Abstract: The present work aims to study the influence of different processing conditions, including temperature, roasting, the use of whole nuts, pressure (nozzle size) and speed of the screw‐press extraction process, on the minor components, mainly tocopherols, phenolics, and volatile components, contained in virgin pistachio oils (VPO) and their corresponding partially defatted residual cakes. An important increase in total polar phenolic (TPP) is observed in VPO processed at a temperature above 60 °C (e.g., 16.7–65.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 56 publications
2
6
0
Order By: Relevance
“…An important increase in acids and alcohols is observed at higher extraction temperature (>100 °C) or employing roasted nuts (e.g., ref. []), as indeed observed in the commercial oils studied (Table ,b), as mentioned above.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…An important increase in acids and alcohols is observed at higher extraction temperature (>100 °C) or employing roasted nuts (e.g., ref. []), as indeed observed in the commercial oils studied (Table ,b), as mentioned above.…”
Section: Resultssupporting
confidence: 83%
“…Table ,b highlights the broad concentration ranges of the volatiles from the different families present in the commercial almond and hazelnut oils, as exemplified by the acids (1.47–21.81 mg kg –1 almonds and 1.44–18.14 mg kg –1 hazelnuts), aldehydes (3.06–7.11 mg kg –1 almonds and 1.86–14.47 mg kg –1 hazelnuts), and alcohols (0.17–4.16 mg kg –1 almonds and 0.00–2.43 mg kg –1 hazelnuts). The high concentration of acids (18.14 mg kg –1 ), as well as the presence of filbertone (5‐methyl‐( E )‐2‐hepten‐4‐one), pyrazines, and furans (data not shown), is probably related to the extraction conditions employed in the commercial oils (mainly high temperatures) and the use of roasted nuts, which contributes to the typical nutty–roasty aroma …”
Section: Resultsmentioning
confidence: 99%
“…In the present work the obtained oil had a total tocopherol content of 1000 mg/kg oil (Table 4), similar to the value obtained by Ojeda-Amador et al, (2018b) from roasted Larnaka pistachio oil (830 mg/Kg), but much higher than Ling et al, (2016) who reported a maximum of 367 mg/Kg oil. In acconcordance with these works g -tocopherol was the most abundant isomer found and in agreement with Ojeda-Amador et al, (2018b), the increase in temperature during the extraction process did not significantly favor tocopherol solubility in oil. With respect to the total phenol contents (TPC) ( Table 4), both extracted oils presented a lower TPC (10.3-11.28 mg GA/Kg oil) than those reported by Rabadán et al, (2017) (24.31 mg GA/kg oil), Ling et al, (2016) (38.7-49.5 mg GA/kg oil) and by Ojeda-Amador et al, (2018b) (approximately 16-76 mg GA/kg).These differences among studies can be attributed to the fact that the TPC of nuts are affected not only by the genotype, but also the orchard location, harvest year, maturity index, processing, and storage conditions (Bolling et al, 2011).…”
Section: Assaysupporting
confidence: 86%
“…In this context, the screw-press extraction technique is as an alternative process to solvent removal, especially for specialty oils because it provides an easy and reliable method of processing seeds and nuts with high oil contents (Wiesenborn et al, 2001;Singh et al, 2002;Zengh et al, 2003;Martínez et al, 2008;2017a;2107b). There are previous studies in which pistachio oil extraction by pressing was analyzed (Alvarez-Ortí et al, 2012;Sena Moreno et al, 2015;Ling et al, 2016;Rabadán et al, 2017;Ojeda-Amador et al, 2018b). Particularly, Rabadán et al, (2017) and Alvarez-Ortí et al, (2012) compared hydraulic and screw-press, and concluded that a higher oil recovery (70 and 40%, respectively) was obtained by screw pressing regardless of the processing conditions.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation